Implementation of XMPP Protocol on Android Pulse Filling Application - Aditiya Hermawan; Agus Setiawan (Tech-E, 2017)
Along with the increasing capabilities of mobile devices, the need for pulses is also growing rapidly. Currently resellers only utilize the technology SMS (Short Message Service) in conventional to conduct transactions. To assist in the more efficient pulse delivery process, it was built using the XMPP protocol. In this study using Extreme Programming design method with 4 (four) stages of process planning, design process, coding process and testing process. The results of testing conducted by using black box testing as well as questionnaires from the resellers, applications that help in the transaction pulse, and improve the efficiency of time in the process of pulse delivery.